Investigating Types of Moral Value in Children of Heaven Movie Directed by Majid Majidi - Sarsono Sarsono; Ardy Satrio Gutomo; Abdulloh Abdulloh; Slamet Basuki (STIBA IEC JAKARTA, 2024)
The Objective of the research is to find out the types of moral values and to find out the most dominant type of moral value in the Children of Heaven movie by Majid Majidi. The writer use descriptive qualitative method to get the objective of the study. The researchers have collected the data from the script of “Children of Heaven” movie by Majid Majidi. In Conclusion of the researcher founding and result there some types of moral values. The categories found are 6 from Caring for other living thing and environment, 3 from Respect and caring for others, 2 from Commitment to something greater than oneself, and 1 from Self-respect, but with humbleness or respect to others, self-discipline, and acceptance of personal responsibility. Faith & Courage values don’t have any dialogue in this movie, but there is a scene for each both Faith and Courage which represent them. And the most dominant moral value occurred in the Children of Heaven movie by Majid Majidi is Caring for other living thing and environment with 6 data.